A method for measuring photopyroelectric spectra of dyes in a polymer pyroelectric matrix - ŁĘTOWSKI, S.; SIKORSKA, A. (Archives of Acoustics, 1992)
A method for measuring pyroelectric spectra of a dye admixed to a pyroelectric matrix has been described. Spectra obtained in the visible range by photopyroelectric and photoacoustic methods have been compared for rhodamine B in the pyroelectric PVDF matrix.